2000
DOI: 10.1007/s001340000675
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities and limits of treatment in patients with thrombotic thrombocytopenic purpura

Abstract: Results of treatment of 18 patients fulfilling the criteria for TTP are presented. Thrombocytopenia was present in all patients (100%). Sixteen of the 18 patients (88.8%) had mental status changes, and seven of the 18 patients (38.8%) had renal impairment. One patient had a secondary type of TTP, caused by non-Hodgkin's lymphoma of the large intestine (that was diagnosed later) and was excluded from the study. Immunosuppresive therapy with steroids, plasma exchange and replacement of removed volume with fresh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…We identified six studies that reported on critically ill patients with TTP (Table 2). 15,16,[39][40][41][42] These populations differed in terms of severity of illness, organ support and mortality, which may be attributable to variation in admission policies across centres.…”
Section: Ttp In the Icumentioning
confidence: 99%
“…We identified six studies that reported on critically ill patients with TTP (Table 2). 15,16,[39][40][41][42] These populations differed in terms of severity of illness, organ support and mortality, which may be attributable to variation in admission policies across centres.…”
Section: Ttp In the Icumentioning
confidence: 99%
“…Currently, plasma exchange (PE) therapy has been the accepted method of treatment in patients with TTP (Bell et al, 1991;Rock et al, 1996;Gasparovic et al, 2000). The benefit of other therapeutic modalities such as steroids and antiplatelet agents in combination with PE has not been conclusively shown (George, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These studies included small numbers of patients and were usually descriptive (17)(18)(19)(20). One retrospective multicenter study investigated factors associated with outcomes for ICU patients with severe TMA and suggested that the means of administration of plasma therapy had a significant impact on the outcome (20).…”
mentioning
confidence: 98%